PENGARUH BIMBINGAN BELAJAR OLEH KELOMPOK SOSIAL KHATULISTIWA BERBAGI TERHADAP PRESTASI BELAJAR ANAK MARJINAL - Rahmatika, Dwi Bintang; Zakso, Amrazi; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research entitled the influence of tutoring by Khatulistiwa Berbagi Social groups on the learning achievements of marginal children in the area of Komplek Waduk Permai Pontianak. This research purpose to find out the influence of tutoring on the learning achievements of marginal children, with the general problem is